Amelioration of adjuvant-induced arthritis by exposure to low dose gamma radiation and resveratrol administration in rats. (2nd July 2020) - El-Ghazaly, Mona A.; Fadel, Noha A.; Abdel-Naby, Doaa H.; Abd El-Rehim, Hassan A.; Zaki, Hala F.; Kenawy, Sanaa A.
Abstract: Purpose: Low dose radiation has been reported as an effective treatment for rheumatoid arthritis via multiple dose exposures. The present study was designed to increase the therapeutic efficacy of low dose radiation with the minimum exposure level in arthritic rats by concurrent administration of resveratrol (RSV) as an adjunctive therapy with anti-inflammatory properties. Materials and methods: Rats were rendered arthritic by sub-plantar injection of Freund's complete adjuvant (FCA) and exposed to low dose radiation at a total exposure level of 0.5 Gy (2 × 0.25). During the exposure course, RSV (50 mg/kg) was orally administered once daily for two weeks. Diclofenac (3 mg/kg) was administered as a standard anti-inflammatory drug. Paw volume was measured every 4 days. After 28 days of induction, rats were sacrificed and serum was collected for estimation of tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), thiobarbituric acid reactive substances (TBARS), and total nitrate/nitrite (NOx ). Furthermore, paws were dissected for histopathological examinations and immuno-histochemical estimation of nuclear factor-kappa B p65 (NF-κB p65) expression. Results: Administration of RSV during the low dose radiation exposure course produced a significant decrease in the paw swelling and a potentiated inhibition in the serum levels of TNF-α, IL-1β, TBARs, and NOx . The dual treatment strategy alleviated the histopathological damage to a greater extent than that produced by each treatment. Moreover, a pronounced suppression of NF-κB p65 expression in the synovial tissue was observed in the combination group. The combination treatment showed a nearly similar potency to that observed in the diclofenac treated group. Conclusion: Administration of RSV augmented the modulatory activity of low dose radiation with minimum exposure level on the disease progression.